La place du paysage dans l’action des parcs naturels régionaux depuis la loi Paysage (1993) - Pierre Dérioz (Projets de Paysage)
An important aspect of the Landscape Law of 08 January, 1993 was the reinforcement of the role and institutional position of Regional National Parks. This reinforcement resulted in new attention being accorded to the landscape in the elaboration of park charters as well as in the use of specific tools proposed in the Law (landscape directives) and activated or reactivated through the extension of its enactment (landscape charters, landscape plans and atlases, photographic landscape observatories, etc.). Still, even if the landscape holds a central place in park actions, here analysed through the cases of five RNP in southern France with which the author has privileged scientific links, the legal obligation for all documents of urbanism to conform to the orientations of the RNP charters has proven more difficult to implement. Exercising their “landscape” mission remains complicated for the RNP, revealing internal tensions proper to these inter-communal bodies and necessarily involving substantial consultation with the actors.